RADIOGRAPHIC STUDY ON THE VISCOSITY OF THE FE-FES MELTS AT THE PRESSURE OF 5 TO 7 GPA - Urakawa S.; Terasaki H.; Kato T.; Funakoshi K.; Suzuki A. (My University, 2001)
Stokes' viscometry combined with in situ X-ray radiographic observation, using the 6-8 type multi-anvil press and synchrotron radiation, has been applied to the viscosity measurement of the Fe-FeS melt up to pressures of 7 GPa. The viscosity is found to be about 2 × 10-2 Pa-s at 5 to 7 GPa and temperatures about 1350 K, in marked contrast to previous viscosity measurements, which showed high viscosity, 0.5 to 14 Pa-s, at 2 to 5 GPa (LeBlanc and Secco 1996). Our viscosity data, however, is consistent with all other evidence, which include I atm viscosity data, X-ray structure analysis, and ab initio simulations. Recent viscosity measurements (Dobson et al. 2000) also showed the viscosity of Fe-FeS melt to be about 10-2 Pa-s at 2.5 GPa. Thus, we are confident that the viscosity of the Fe- FeS melt is close to a typical value (10-2 Pa-s) of viscosity for liquid metal even at high pressures.